1987
DOI: 10.1139/z87-266
|View full text |Cite
|
Sign up to set email alerts
|

Auditory recognition of covey mates from separation calls in Northern Bobwhite (Colinus virginianus)

Abstract: Two experiments were conducted to determine whether Northern Bobwhite (Colinus virginianus) discriminate covey mates from noncovey mates on the basis of recognition of the individual giving the separation call. Two possible modes of recognition, phenotype matching and call association, were tested. Artificially and naturally hatched quail chicks from two familial lines of linebred quail and quail of crossed lines were reared and tutored by either a related or an unrelated adult. Chicks were separated one at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Two other studies have published data on nonlearned bird vocalizations from which broad‐sense heritabilities can be calculated. Duration and frequency characteristics of separation calls of northern bobwhites showed an average heritability of 56% (calculated from table 3 in Baker and Bailey 1987), and those of nestling begging calls showed heritabilities of around 60% in barn swallows and 93% in cliff swallows (calculated from Table 1 in Medvin et al 1992). Hence, in nonlearned vocalizations, heritabilities of around 60% seem to be the default, and the increased value in cliff swallows might be interpreted as resulting from selection increasing between‐brood differences to facilitate offspring recognition in these colonial breeders (Medvin et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies have published data on nonlearned bird vocalizations from which broad‐sense heritabilities can be calculated. Duration and frequency characteristics of separation calls of northern bobwhites showed an average heritability of 56% (calculated from table 3 in Baker and Bailey 1987), and those of nestling begging calls showed heritabilities of around 60% in barn swallows and 93% in cliff swallows (calculated from Table 1 in Medvin et al 1992). Hence, in nonlearned vocalizations, heritabilities of around 60% seem to be the default, and the increased value in cliff swallows might be interpreted as resulting from selection increasing between‐brood differences to facilitate offspring recognition in these colonial breeders (Medvin et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…From studies of hybridization and interspecific cross‐fostering it is clear that many vocal traits show a hereditary basis (Baptista 1996; Derégnaucourt et al 2001). However, very few studies have estimated the heritability of vocal traits within a population (Zann 1985; Baker and Bailey 1987; Medvin et al 1992). Songbirds are particularly interesting to study in that respect, because their vocal repertoire comprises innate calls, as well as learned calls and songs.…”
mentioning
confidence: 99%
“…We found a significant relationship between the kinship coefficients of captive houbara males and the frequency parameters, the frequency modulation and the duration of their booms, suggesting that several features of the booms are to some degree heritable through genetic transmission in this species. In other bird species, frequency and temporal acoustic parameters have been found to be genetically inherited as, for example, in the calls of northern bobwhites Colinus virginianus (Baker & Bailey, ) and in the begging calls of barn swallows Hirundo rustica and cliff swallows Petrochelidon pyrrhonota (Medvin, Stoddard, & Beecher, ). In vertebrates, call structure similarity between related individuals is often the outcome of inherited morphological, physiological, and neurological characters involved in call production (Bradbury & Vehrencamp, ).…”
Section: Discussionmentioning
confidence: 99%
“…Individual and sexual differences in call structures were discovered in many monomorphic bird species (e. g. Schwanke & Rutschke 1988, Hausberger et al 1991, Carlson & Trost 1992, Nuechterlein & Buitron 1992, Allenbacher et al 1995, Mathevon 1996, Ballintijn & ten Cate, 1997, Guyomarc'h et al 1998, May 1998, Charrier et al 2001a. Numerous playback experiments confirmed that responses to the calls of familiar individuals (mates, parents and offsprings) did differ significantly from responses to the calls of unfamiliar birds (e. g. Baker & Bailey 1987, Clapperton 1987, Jones et al 1987, Jouventin et al 1999, Aubin et al 2000, Charrier et al 2001b, Lengagne et al 2001.…”
Section: Introductionmentioning
confidence: 98%